Peran Sekolah Ramah Anak dalam Mencegah dan Menangani Perundungan Peserta Didik - Ningrum, Ayu Reza; Hidayah, Nurul; Hidayah, Nur; Suryani, Yani; Hasanah, Uswatun (AR-RIAYAH: Jurnal Pendidikan Dasar, 2024)
This research aims to determine the form of bullying that occurs at SDN 01 Sabah Balau, South Lampung and what the role of child-friendly schools is in dealing with and dealing with bullying that occurs. The type of research used in this research is descriptive qualitative. Where this type of research uses existing theories or can even produce new theories. The approach in this research is a case study. Data collection techniques use interviews, observation and documentation. The data analysis technique used is the Miles and Huberman model. The results of the research show that the forms of bullying that occur at SDN 01 Sabah Balau are verbal and physical. Verbal bullying such as ridiculing or insulting friends with inappropriate words. Meanwhile, physical bullying takes the form of hitting, pinching and pushing friends. Furthermore, the role of schools in overcoming and overcoming bullying that occurs is through several things such as implementing several strategies such as varying learning spaces, instilling character values through integrating subjects, anti-bullying socialization and education as role models.